Acute and chronic effects of exercise on circulating endothelial progenitor cells in healthy and diseased patients - Volaklis, Konstantinos A.; Tokmakidis, Savvas P.; Halle, Martin (Clinical Research in Cardiology, 2013)
Exercise is known to improve endothelial function in healthy subjects as well as patients with cardiovascular disease and this might be partially related to a regeneration of diseased endothelium by circulating progenitor cells (EPCs). EPCs are a subgroup of peripheral blood monocytes that contribute to re-endothelialization of injured endothelium as well as neovascularization of ischemic lesions. Cross-sectional studies have indicated that chronic, regular physical activity has a positive effect on the levels of circulating EPCs. This is associated with an improvement of endothelial dysfunction that is induced by apoptosis due to the underlying aging process or accelerated by cardiovascular risk factors. Furthermore, it is well established that chronic exercise training has the potency to mobilize EPCs from the bone marrow. For patients with cardiac disease this is of clinical importance since EPCs have been implicated in vascular repair and revascularization. Studies are needed to refine the best mode of exercise training that will upregulate circulating EPCs as well as to clarify the kinetics of EPCs after the termination of different exercise sessions in different diseases and medication. Whether there is a direct link between enhanced mobilization of EPCs via exercise and improvement of disease and prognosis remains a hypothesis which needs to be further evaluated. © 2012 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acute exercise; Chronic exercise; Endothelial progenitor cells